Impact of rigorous nursing training and reinforcement on incidence of thrombophlebitis at tertiary care centre - Purushothaman, Suraj; Patel, Kinjal P.; Dalal, Dhaval N.; Carwal, Trupti N.; Gawali, Vijaykumar P. (International Journal of Advances in Medicine, 2020)
Background: Peripheral venous cannulation (PVC) is one of the commonest procedures carried out in hospital. It allows rapid and accurate administration of medication. However, there is dearth of formal training to nurses There are few studies which has shown benefits of offering formal training to improve clinical practice and patient care. Methods: In view of rising cases of thrombophlebitis, nurses were trained in hand hygiene, patient skin preparation, wearing gloves and aprons, establishing a clean environmental field, using sterile equipment, disposing of contaminated or soiled equipment and linen appropriately, safe disposal of sharps and adherence to universal precautions. Retrospective, observational, single centre study to analyse data of inpatients for 4 years duration was carried out. This included 2 years data prior to offering nursing training and 2 years post training. Results: There is statistically significant improvement in number of thrombophlebitis event for 2 years prior and 2 years post training. Total events in 2 years prior to training were 63 which reduced to 22 in later 2 years due to nursing training. A p value was 0.0297. Out of total 87 thrombophlebitis incidences, 40 and 47 incidences in males and females respectively were observed. Mean age for men was 58.39 and mean age for female was 52.62 with SD 27.39 and 22.06 respectively. Conclusions: When nurses were trained in patient assessment, Insertion site selection (prefer hand and forearm; to avoid joints and lower limbs), catheter selection, dwell time, early identification of phlebitis and appropriate corrective measures and compliance with best practice guideline, thrombophlebitis rates drastically reduced.